Computational and in vitro evaluation of sumac-derived ©Rutan compounds towards Sars-CoV-2 Mpro inhibition - Kayumov, Muzaffar; Marimuthu, Parthiban; Razzokov, Jamoliddin; Mukhamedov, Nurkhodja; Asrorov, Akmal; Berdiev, Nodir S.; Ziyavitdinov, Jamolitdin F.; Yashinov, Ansor; Oshchepkova, Yuliya; Salikhov, Shavkat; Mirzaakhmedov, Sharafitdin (Frontiers in Pharmacology, 2025)
The emergence of the SARS-CoV-2 virus caused the COVID-19 outbreak leading to a global pandemic. Natural substances started being screened for their antiviral activity by computational and in-vitro techniques. Here, we evaluated the anti-SARS-CoV-2 main protease (Mpro) efficacy of ©Rutan, which contains five polyphenols (R5, R6, R7, R7’, and R8) extracted from sumac Rhus coriaria L. We obtained three fractions after large-scale purification: fraction 1 held R5, fraction 2 consisted of R6, R7 and R7’, and fraction 3 held R8. In vitro results showed their anti-Mpro potential: IC50 values of R5 and R8 made 42.52 µM and 5.48 µM, respectively. Further, we studied Mpro-polyphenol interactions by in silico analysis to understand mechanistic extrapolation of Rutan binding nature with Mpro. We extensively incorporated a series of in silico techniques. Initially, for the docking protocol validation, redocking of the co-crystal ligand GC-376* to the binding pocket of Mpro was carried out. The representative docked complexes were subjected to long-range 500 ns molecular dynamics simulations. The binding free energy (BFE in kcal/mol) of components were calculated as follows: R8 (−104.636) > R6 (−93.754) > R7’ (−92.113) > R5 (−81.115) > R7 (−67.243). In silico results of R5 and R8 correspond with their in vitro outcomes. Furthermore, the per-residue decomposition analysis showed C145, E166, and Q189 residues as the hotspot residues for components contributing to maximum BFE energies. All five components effectively interact with the catalytic pocket of Mpro and form stable complexes that allow the estimation of their inhibitory activity. Assay kit analyses revealed that Rutan and its components have effective anti-SARS-CoV-2 Mpro inhibitory activity.